Thermosolutal instability in compressible viscoelastic dusty fluid through porous medium - Kumar, Pardeep; Mohan, Hari (Zielona Góra: Uniwersytet Zielonogórski)
Thermosolutal instability in a compressible Walters B` viscoelastic fluid with suspended particles through a porous medium is considered. Following the linearized stability theory and normal mode analysis, the dispersion relation is obtained. For stationary convection, the Walters B` viscoelastic fluid behaves like a Newtonian fluid and it is found that suspended particles and medium permeability have a destabilizing effect whereas the stable solute gradient and compressibility have a stabilizing effect on the system. Graphs have been plotted by giving numerical values to the parameters to depict the stability characteristics. The stable solute gradient and viscoelasticity are found to introduce oscillatory modes in the system which are non-existent in their absence.
Keywords: thermosolutal instability; compressible Walters B` viscoelastic fluid; suspended particles; porous medium